Nordic Administrative Reforms
XVI, 236 p. 6 illus., 4 illus. in color.
Keywords: This book is based on a unique data set and assesses in comparative terms the public management reforms in the five Nordic countries: Denmark, Finland, Iceland, Norway, and Sweden. Based on the assessments of administrative executives, the book compares the Nordic countries with the Anglo-Saxon, the Germanic, the Napoleonic and the East European group of countries. The book addresses the following questions: What reform trends are relevant in the public administrations of the Nordic countries? What institutional features characterize the state authorities in these countries? What characterizes the role identity, self-understanding, dominant values, and motivation of administrative executive in the Nordic countries? What characterizes reform processes, trends and content, what is the relevance of different types of management instruments, and what are their perceived effects and the perceived performance of the public administration? The book also examines how the different Nordic countries dealt with the financial crisis of 2008, and how the differences and similarities in their approaches can be explained. Carsten Greve is Professor of Public Management and Governance at the Department of Business and Politics, Copenhagen Business School, Denmark. He is also Academic Director of the CBS Public Private Platform. His research interests include public management reform and public-private partnerships in an international perspective. He teaches at the executive Master of Public Governance program in Copenhagen. Per Lægreid is Professor at the Department of Administration and Organization Theory, University of Bergen, Norway. He has published extensively on public sector reform, public management and institutional change from a comparative perspective. His latest publications include articles in Governance, Public Administration, International Review of Administrative Science, Public Administration Review and Public Management Review. Lise H. Rykkja is Senior Researcher at the Uni Research Rokkan Centre, Norway. Her research concentrates on the organization and development of public administration and public policies based in a broad institutional and comparative perspective. Her latest publication includes articles in Public Administration, Public Administration Review, Public Management Review and International Journal of Public Administration.